Efecto del liofilizado de Corryocactus brevistylus "sanky" en lipoperoxidación inducida en membranas eritrocíticas humanas - Gallardo Coronado, Yudith (2017)
ABSTRACT The antioxidant effect of Corryocactus brevistylus "sanky" on lipoperoxidation induced through hydrogen peroxide in human erythrocyte membranes was investigated, the production of malondialdehyde (MDA) was the final indicator of the lipoperoxidation process. The sample size consisted of 20 volunteers, without prior medication, as well as a diet free of roasted meat, Fried, grilled and without alcohol consumption from one week before the study. 5 mL of blood was extracted from each patient and for the design of the working groups each sample was exposed to each of the following substances; Control Group (phosphate buffered saline), Standard Group (125 μM/mL trolox), Problem 1 Group (250 μg/mL sanky) and Problem Group 2 (500 μg/mL sanky). The levels of MDA in erythrocytic membranes were determined through the colorimetric method of thiobarbituric acid reactive substances (TBARS), and final measurement by absorption spectrophotometry at 532 nm of wavelength. It was concluded that sanky at doses of 250 and 500 μg/mL presented antioxidant effect as a decrease in malondialdehyde levels in human erythrocyte membranes (p < 0,05).